An Improved and Practical Method for Synthesizing of α-Sanshools and Spilanthol - Nakamura, Akira; Mimaki, Kazuki; Tanigami, Ken-ichi; Maegawa, Tomohiro (Frontiers in Chemistry, 2020)
An efficient and practical route for the synthesis of hydroxy-α-sanshool is described herein. Several modifications of an existing method enabled the preparation of the (2E,6Z,8E,10E)-tetraene precursor of hydroxy-α-sanshool in good yield. A highly selective Wittig reaction employing newly synthesized phosphonium salt with low deliquescence and long-term stability yielded the desired Z-form tetraene. This improved methodology was shown to be applicable to the efficient synthesis of α-sanshool and spilanthol.